2022
DOI: 10.26599/tst.2020.9010056
|View full text |Cite
|
Sign up to set email alerts
|

Combining residual attention mechanisms and generative adversarial networks for hippocampus segmentation

Abstract: This research discussed a deep learning method based on an improved generative adversarial network to segment the hippocampus. Different convolutional configurations were proposed to capture information obtained by a segmentation network. In addition, a generative adversarial network based on Pixel2Pixel was proposed. The generator was a codec structure combining a residual network and an attention mechanism to capture detailed information. The discriminator used a convolutional neural network to discriminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Our review of the literature [8][9][10][11][12][13][14] revealed the following shortcomings in the above models (methods):…”
Section: Improving a Neural Network Model For Semantic Segmentation Of Images Of Monitored Objects In Aerial Photographsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of the literature [8][9][10][11][12][13][14] revealed the following shortcomings in the above models (methods):…”
Section: Improving a Neural Network Model For Semantic Segmentation Of Images Of Monitored Objects In Aerial Photographsmentioning
confidence: 99%
“…Study [9] proposed various models based on convolutional neural networks (CNNs) to collect information obtained using a segmentation network; a generative adversarial network based on Pixel2Pixel was suggested. The discriminator employed CNN to distinguish between the results of segmentation of the generated model and the Expert Advisor.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It also reduces costs, and energy consumption, etc [4].To sum up, CNN is an organic combination of neural network and traditional depth machine learning technology. It can conduct adaptive training on images, so that its weight in convolutional neural network can be effectively improved [5]. CNN is superior to traditional neural networks in fault tolerance, adaptability, self-learning ability, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is expected to decrease the workload on medical professionals and reduce the frequency of patient visit and waiting time. Many recent studies ( Basaia et al, 2019 ; Bi et al, 2020 ; Jiang et al, 2020 ; Guo et al, 2021 ; Hett et al, 2021 ; Mehdipour Ghazi et al, 2021 ; Deng et al, 2022 ) have been conducted to forecast early stages of Alzheimer’s disease. The goal of this study is to build a computer-aided system based on a deep learning algorithm to evaluate the pathological brain structural changes in MRI data in order to forecast the early stages of Alzheimer’s disease before it progresses to the severe stages.…”
Section: Introductionmentioning
confidence: 99%